The phylogenetics and evolution of Africa's Larks (Alaudidae) - Barnes_KN (Department of Philosophy, 2024)
The larks are a group of dull coloured birds that are conservative in plumage coloration and pattern due to the requirements for camouflage in open habitats. Because many species inhabit structurally similar habitats the group is also characterised by a great deal of morphological convergence. Variation in plumage and morphology is frequently as great within species as it is between species, leading to many inconsistent and controversial taxonomic treatments and classifications at an intra- and inter-generic level, and when defining specific and sub-specific boundaries. The advent ofgenetic techniques and success at applying these to species complexes in southern Africa suggested that a molecular phylogeny of the family would elucidate relationships that could not be determined via traditional taxonomic practices. In this study 2009 nucleotides oftwo mitochondrial DNA genes, cytochrome b and 16S rRNA (Chapter 2), and 2872 nucleotides of the nuclear exon RAG-l (Chapter 3) were used to generate a robust phylogeny ofthe family Alaudidae. The former analysis included 55 species and the latter 25. These data were also combined to construct a combined evidence phylogeny (Chapter 7). Within the family, several genera recognised by more traditional taxonomies are polyphyletic, including Ammomanes, Eremalauda .and Certhilauda. Two other genera, Calandrella and Mirafra, are best treated as multiple genera (Chapter 2). The sampled Alaudidae can be divided into three main radiations, the ammomanid larks, mirafrid larks and alaudid larks (Chapter 3). Within the ammomanid larks, there is strong support for: (1) a southern African'radiation comprising Chersomanes, t h e L o n g - b i l l e d L a r k c o m p l e x (Certhilauda) a n d Ammomanes (Ammomanopsis) grayi ,with Alaemon allied to this radiation; and (2) a .Saharo-Sindian radiation comprising Ramphocoris c1otbey, Ammomanes cinc(urus, and A. deserti sister to the Afro-Sindian sparrowlark Eremopterix clade. The Madagascan endemic Mirafra hova was a surprise basal member of Eremopterix. The mirafrid larks comprise a moderately strong association, between the genera Mirafra (occurring at many nodes within the clade), Heteromirafra, and members of the Karoo-Red lark complex often placed in Certhilauda (Chapters 2 & 3). Due to the diversity in this assemblage it is recommended that the mirafrid larks be reconstructed to comprise the genera Calendulauda (pipit-like Mirafra with the Karoo-Red Lark complex), Heteromirafra, Mirafra (the finch-like Mirafra), Corypha (the 'insectivorous' Mirafra) and Megalophoneus (the strange Flappet Lark). Finally, the alaudid larks, comprised a merger of eight traditionally classified genera and contained two main clades: (l) a strong association between Alauda and Galerida, while supporting Lullula as a distinctive monotypic genus, more closely related to Afrotropical Spizoco1')'s; and (2) a poorly resolved association comprising Eremalauda, Eremophila, Calandrella (and Alaudula) and Melanocorypha (Chapters 2, 3 & 7). A study using toe pads from museum skins (278 nucleotides of cytochrome b) assessed the placement of six species of scarce and infrequently encountered larks traditionally placed in Mirafra (Chapter 4). Each species was associated with one ofthe lineages identified in the multi-generic mirafrid larks (Chapters 2, 3 & 7). Mirafra collaris was nested within Calendulauda. The genus Corypha included angolensis and ashi as sister taxa and in some analyses a super-species of somalica, africana and hypermetra was postulated. The genus Mirafra (sensu stric,tu) comprised M albicauda and M cheniana as strongly supported sister taxa (Chapter 4). Mirafra pulpa was most closelyrelatedtoM williamsi. A more detailed analysis of eleven subspecies of the highly resident insectivorous Spike-heeled Lark Chersomanes albofasciata complex was conducted (Chapter 5) using- 630 bps of the cytochrome b gene. The geographically isolated Tanzanian taxon beesleyi is genetically highly distinct, differing by 4.9-6.2%. Well-defined morphological and I. behavioural differences supported full species designation of Beesley's Lark C. beesleyi which was basal within Chersomanes, su ggesting that it is an ancient relict species isolated in East·Africa several million years ago possibly by the processes ofarid corridor vicariance. A conservation assessment of Beesley's Lark (Chapter 6) showed it to be Critically Endangered with a range of 40-65 km2 and an estimated global population of 92-286 individuals. For South African Chersomanes albofasciata, three distinct populations were recognized. Phylogenetic and haplotype analyses show tJie geographically isolated Eastern alticola and Namaqualand garrula were more closely related to one another than either was to the adjacent Karoo albofasciata, reflecting a biogeographic pattern similar to that shown by the sister Long-billed Lark complex (Chapter 5). It was R.E. Moreau who first mooted the idea that the arid zones o f southwest and northeast Africa could have been linked during climatic times of extreme aridity. The postulation of an arid corridor has led many to speculate that larks and other arid-zone taxa could have dispersed across Africa, and that sister taxa subsequently speciated via processes of vicariance. This hypothesis was examined in light of the lark phylogenies. Resident arid-zone taxa seem to have evolved in-situ, with lark complexes, particularly in southern Africa, being more closely related to one another than to taxa that look morphologically similar (convergent) in East or North Africa. Dispersal via an arid coIJidor n6'Wever seems more likely for species favouring arid savanna, grassland or . ---~~remesic habitats, or migratory or nomadic species rather than highly sedentary desert and semi-desert larks (Chapters 2 & 7). A study examining the evolution o f biological traits within the family (Chapter 7) showed that many traits are conservative and restricted to, or typical of, certain phylogenetic lineages (particularly within the ammomanid and mirafrid larks) or modes of life. Insectivorous larks tend to be highly resident and sexually size dimorphic, while nomadism, partial migration, Palearctic or intra-African migration are developed as strategies to adapt to a diet including a large seed component. Desert specialist larks are either resident insectivores or locally nomadic/partially migrant seed-eaters that exploit temporarily abundant resources. The thesis develops a new classification for the Alaudidae (Chapters 2 & 7) and shows convincingly that many robust hypotheses about the evolution of the family can be formulated. However, much work remains, and it appears evident that in the Alaudidae many cryptic species complexes await discovery.